Creación de una microempresa de elaboración artesanal de mermeladas para diabéticos, plan de negocios, marca, ingreso al mercado - Chávez Romero, Fernando Marcelo (2012)
This food proposal pretends to develop jams fruits and vegetables using a mix of oranges, carrots and naranjilla whit zapallo for diabetics. Whit fruits and vegetables are rarely in jams. The idea is to offer an alternative of a healthy jam, to the costumer. There are a huge variety of jams, in the market but for diabetics doesnt, exist an option, therefore we want to offer a delicious and healthy product without exceeding the adequate portion.